Clinical Pattern of Viral Fever in Children: Is Rational Antibiotic Use Possible in Non-Critical Hospitalized Children in Resource Limited Setting? - Vasavada, Halak; Parmar, Panchshila; Parmar, Vishesh; Prajapati, Kundan; Modi, Neha; Patel, Disha (National Journal of Community Medicine, 2017)
Introduction: Most of Viral infections in non-critical children are self-limiting. Yet, many times, due to lack of clinical knowledge, antibiotics are prescribed which leads to antimicrobial resistance. Aim is to study the demographic and clinical profile and outcome in non-critical children admitted with suspected viral infection. Materials and method: It was a prospective observational study carried out in the pediatric ward of Shardaben Hospital between November 2014 and August 2015. Results: Out of the total 3143 patients, 1760(56%) were non-critical with suspected viral infection on admission. The fever was regular in 89% patients, while 88% patients got better on 3rd day of admission. 82% children were not sick in the inter-febrile period. The fever was high grade at onset in 75% patients and 91% responded to paracetamol. In 4.6% of patients fever found to be non-viral but none of the patients required PICU care. There was no mortality. Conclusion: Viral fever is usually high grade at onset, with non-sick inter-febrile period and natural improvement by 3rd or 4th day of illness. With these clues, viral infection can be suspected and antibiotic misuse can be avoided even in hospitalized children.